Minutes of Meeting Reviewing the Shore Establishment Realignment (1973)
The minutes for a meeting in the Naval Air Command in Washington, D.C. discussing the Shore Establishment Realignment. Includes a list of attendees and describes different decisions made in regards to the SER.